"The Effect of Price Discrimination Practices on New and Existing Clients in a Service Setting" - Teresa Fernandes (2014)
Price discrimination is the practice of offering different prices to present and prospective customers. The purpose of our paper is to investigate the main effects of price discrimination practices of service firms on clients, measured by perception of unfairness and its impact on satisfaction and trust and, in turn, loyalty. Drawing on the theory of distributive justice (Homans, 1961) and the equity theory (Adams, 1965), this study aims to show a dual perspective: the perception of unfairness of new vs existing clients when they face the advantaged or disadvantaged conditions. As such, we contribute to a better understanding of potential interaction effects between new client acquisition and retention efforts of existing customers, through price discrimination. In managerial terms, our paper aims to help service firms to better design and implement their customer management strategies when using price segmentation practices.